1979
DOI: 10.1136/jnnp.42.6.548
|View full text |Cite
|
Sign up to set email alerts
|

Centronuclear myopathy.

Abstract: The patient (CM), a black girl aged 7 years, is the only child of a non-consanguineous marriage. Pregnancy and delivery were normal. In the early neonatal period, transient jaundice was present. A generalised floppiness was noted soon after birth with reportedly normal limb movements. There were no feeding difficulties and bulbar function appeared to be good. Considerable difficulty in lifting the head, especially when in the prone position, was noted after a few months. She was able to sit unaided at the age … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
6
0

Year Published

1982
1982
1998
1998

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 14 publications
3
6
0
Order By: Relevance
“…Type I fiber predominance, one of the main findings in CNM [3][4][5]11,12,15,16 , was seen in all our muscle samples. Four patients disclosed only type I fibers.…”
Section: Fig 3 the Central Nucleus (N) With Multilobulated Aspect Issupporting
confidence: 52%
See 4 more Smart Citations
“…Type I fiber predominance, one of the main findings in CNM [3][4][5]11,12,15,16 , was seen in all our muscle samples. Four patients disclosed only type I fibers.…”
Section: Fig 3 the Central Nucleus (N) With Multilobulated Aspect Issupporting
confidence: 52%
“…Only one patient of our series had a severe increase and in the other patients it was absent or insignificant. Other authors have found an increase in the endomysial, or perifascicular adipose tissue 2,3,4,14,30 . Only an increase in the perifascicular adipose tissue we have found in our patients.…”
Section: Discussion Discussion Discussion Discussion Discussionmentioning
confidence: 89%
See 3 more Smart Citations